2014
DOI: 10.1039/c3em00544e
|View full text |Cite
|
Sign up to set email alerts
|

Formation and release behavior of iron corrosion products under the influence of bacterial communities in a simulated water distribution system

Abstract: To understand the formation and release behavior of iron corrosion products in a drinking water distribution system, annular reactors (ARs) were used to investigate the development processes of corrosion products and biofilm community as well as the concomitant iron release behavior. Results showed that the formation and transformation of corrosion products and bacterial community are closely related to each other. The presence of sulfate-reducing bacteria (SRB, e.g. Desulfovibrio and Desulfotomaculum), sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…The effect of disinfection on the community composition has previously been reported, indicating that Alphaproteobacteria are typically dominant in both chlorinated and chloraminated water, whereas Betaproteobacteria were found to have increased abundance in chloraminated water as opposed to chlorinated water (Berry, 2006;Wang et al, 2014). This was consistent with the observed changes in Alpha-and Betaproteobacteria in this study.…”
Section: Effects Of Dwds Configuration and Disinfection On Bacterial supporting
confidence: 92%
See 2 more Smart Citations
“…The effect of disinfection on the community composition has previously been reported, indicating that Alphaproteobacteria are typically dominant in both chlorinated and chloraminated water, whereas Betaproteobacteria were found to have increased abundance in chloraminated water as opposed to chlorinated water (Berry, 2006;Wang et al, 2014). This was consistent with the observed changes in Alpha-and Betaproteobacteria in this study.…”
Section: Effects Of Dwds Configuration and Disinfection On Bacterial supporting
confidence: 92%
“…However, it is difficult to separate the effect of a single parameter on the bacterial community in a fullscale DWDS. For example, Wang et al (2014) reported on the combined effects of disinfectant, water age and pipe material creating different physicochemical conditions and ecological niches, which can then select and promote the growth of various microbes.…”
Section: Effects Of Dwds Configuration and Disinfection On Bacterial mentioning
confidence: 99%
See 1 more Smart Citation
“…Unwanted changes in microbial quality of drinking water can have adverse effects on distribution system and consumers. For example, during distribution, excessive growth of bacteria can lead to deterioration of drinking water quality in terms of safety (e.g., pathogens), consumer’s perception (e.g., discolouration) and operational aspects (e.g., biocorrosion; Szewzyk et al, 2000 ; Vreeburg et al, 2004 ; Sun et al, 2014 ). Changes in microbial water quality are a result of complex interactions between various organisms (bacteria, viruses, protozoa, higher organisms) regulated by: access to available growth-limiting nutrients, response to environmental conditions, such as water temperature, presence of potential residual disinfectant and other inhibitory substances, attachment of bacteria to pipe walls, particle deposition, sediment re-suspension and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SRB, acetogens, iron-reducers/oxidizers, sulfide-oxidizers and methanogenic archaea (MA) are also corrosive (Dinh et al, 2004;Mori et al, 2010;Park et al, 2011;Sun et al, 2014;Kato et al, 2015;Mand et al, 2016). MA can metabolize limited substrates for growth, including H 2 /CO 2 , acetate, methanol and methylamines (Youssef et al, 2009;Tucker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%